PERFORMANCE OF SILICON SOLAR CELL WITH VARIOUS SURFACE TEXTURES - Jahanshah, F; Sopian, K; Ahmad, I.; Othman, M.Y; Zaidi, S.H (185P -3466)
The performance of solar cell with various surface texture patterns was reported. Wet, RIE, one and two dimensions texturing with and without the nitride antireflection coating were compared. An I-V tester calibrated by Sandia National Laboratory was used. The surface texture of the solar cells were as follows (a) solar cell with 2D texturing without nitride antireflection, (b) solar cell with 1D texturing with nitride antireflection (c) solar cell with 1D texturing without nitride antireflection, (d) solar cell with wet texturing without nitride antireflection, (e) solar cell with wet texturing with nitride antireflection (f) solar cell with RIE texturing with nitride antireflection. RIE and two dimension surface texturing showed the best output with maximum short density current of 0.042 mA/cm2 and of 0.045 mA/cm2 respectively.